Cortical dysfunction in patients with Huntington's disease during working memory performance - Wolf, Robert C. (Hum Brain Mapp, 2008)
Previous functional neuroimaging studies on executive function suggested multiple functionally aberrant cortical regions in patients with Huntington's disease (HD). However, little is known about the neural mechanisms of working memory (WM) function in this patient population. The objective of this study was to investigate the functional neuroanatomy of WM in HD patients. We used event‐related functional magnetic resonance imaging and a parametric verbal WM task to investigate cerebral function during WM performance in 16 healthy control subjects and 12 mild to moderate stage HD patients. We excluded incorrectly performed trials to control for potential accuracy‐related activation confounds. Voxel‐based morphometry (VBM) was used to control for confounding cortical and subcortical atrophy. We found that HD patients were slower and less accurate than healthy controls across all WM load levels. In addition, HD patients showed lower activation in the left dorso‐ and ventrolateral prefrontal cortex, the left inferior parietal cortex, the left putamen, and the right cerebellum at high WM load levels only. VBM revealed gray matter differences in the bilateral caudate nucleus and the thalamus, as well as in inferior parietal and right lateral prefrontal regions. However, volumetric abnormalities in the patient group did not affect the activation differences obtained during WM task performance. These findings demonstrate that WM‐related functional abnormalities in HD patients involve distinct WM network nodes associated with cognitive control and subvocal rehearsal. Moreover, aberrant cortical function in HD patients may occur in brain regions, which are relatively well preserved in terms of brain atrophy. Hum Brain Mapp, 2009. © 2008 Wiley‐Liss, Inc.